Resonant soft X-ray spectroscopic studies of certain transition metal oxides - Kennedy, Brian (Trinity College (Dublin, Ireland). School of Physics, 2011)
Rutile-type transition-metal oxides are extremely fertile areas of study both for fundamental and technological reasons due to the range of physical properties they present, such as insulating TiO2, semiconducting Sn02 and metallic RuO2. The chemical bonding of such rutile-type oxides is assumed to have an essentially ionic character despite differences in the outer electronic structures of the cations, from empty outer shell (Ti 4+), to partially filled (Ru 4+) to filled (Sn 4+), but has been shown to become progressively more covalent, and details of their electronic structure are still under intense experimental study and theoretical consideration. To this end, resonant x-ray absorption and emission spectroscopy (RXES) provides a sensitive element-specific and symmetry-selective probe of the unoccupied and occupied electronic bandstructure of these materials.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin.